Juvenile safeguards during the criminal investigation in the Saudi Law and Islamic Jurisprudence - Alqahtani, Yahya Mushabbab (Journal of Economic, Administrative and Legal Sciences, 2022)
This research illustrates the legal and constitutional safeguards for the juvenile during the criminal investigation which is a concern that is being taken care of by Saudi lawmaker in the modern juvenile justice system by issued royal decree no. M/113, August 1, 2018. However, one of the most crucial safeguards is that the prosecution shall only question a juvenile with the presence of his/her guardian or a person acting in such a capacity, a social researcher or worker, or an attorney. Furthermore, a juvenile’s trial shall be conducted before the court in his/her presence and the presence of his/her guardian or a person acting in such a capacity, or, if not possible, a representative from the home. Moreover, the Saudi lawmaker has provided, the juvenile shall not be treated cruelly during his/her trial. In addition, I have found through this research that the Saudi lawmaker has provided solid legal guarantees during the accusation and the investigation of a juvenile. Significantly, the Islamic jurisprudence has taken care of the juvenile even before these legal guarantees took place, as it has differentiated between a male juvenile and a female juvenile and provided more guarantees for them. Therefore, one of the most important safeguards is to prevent seclusion when questioning a woman as well as asking her directly. Hence, this signifies the compliance in most of the safeguards between the Saudi law and the Islamic jurisprudence since the law is made based on the the Islamic jurisprudence.